Imagen, medios y telecolonialidad: hacia una crítica decolonial de los estudios visuales - León, Christian (AISTHESIS: Revista Chilena de Investigaciones Estéticas, 2012)
This paper discusses the visuality processes in Latin America since the called «decolonial turn» approach. It analyzes the structural relationship between visual practices and global power arising in the context of the modern world system. It seeks to study the relationship between visual technologies, discourses and practices and the analytics of the coloniality of power, knowledge and being. It addresses the different types of hierarchies produced through a visual dispositive in the context of the international division of technology labor, the racialization of the population, and the global economy of images.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-TV; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé